Effectiveness of Mechanical Wave Learning Material Based on ICT Integrated CTL to Improve Students Learning Outcomes - Asrizal Asrizal; Auvi Winandri Utami (Postgraduate, University of Mataram, 2021)
The 21st-century skills integrate life career skills, learning and innovation-4C, and information, media, and technology skills. The components are required to make the learning process more effective and efficient. 21st-century learning is transforming from teacher center to student center. Student-centered learning can use ICT-based learning material in the learning process. Based on preliminary research, the use of ICT-based learning material was still low. The solution to this problem was developing learning material based on ICT integrated CTL to improve student's learning outcomes. The method that used in this research was quasi-experiment. The sample in the field testing of learning material based on ICT was a grade XI of students at SMAN Lubuk Sikaping. The data collection instruments used were attitude observation sheets, written tests, and performance assessment sheets. The data analysis techniques used were descriptive statistical analysis, normality test, homogeneity test, and t-test. Based on data analysis, it can be stated that the application of mechanical wave learning material based onÂ ICT integrated CTL Â has a significant effect on students' learning outcomes, including in the aspects of attitudes, knowledge, and skills. This result indicates that the use of mechanical wave learning material based on ICTÂ integrated CTL effectively improves students' learning outcomes